The prevalence and characteristics of incidental colorectal polyps in patients undergoing colonoscopy at a South African tertiary institution - Kruger, Jean-Jacques (Department of Medicine, 2023)
Background There is a lack of data on the frequency, and pattern of colorectal adenomas in subSaharan Africa, to guide diagnostic and preventative strategies for CRC in the region. This study aimed to describe polyp characteristics, and adenoma frequency in patients at average risk of CRC undergoing colonoscopy for bowel symptoms at a tertiary hospital in South Africa. Methods Colonoscopy records from the prospective endoscopy database at Groote Schuur Hospital for the period August 2014 to February 2017 were retrieved. The presence of polyps, and their morphology, size, site and number in relation to ethnicity, symptoms, and colonoscopy quality indicators were analysed. The histological type and grade were obtained from laboratory records, and analysed. The primary endpoint was the adenoma detection rate. Age, gender, ethnicity, symptoms, bowel preparation, and caecal intubation rates were also compared between patients with adenomas, and those without adenomas. Results Of 1334 colonoscopies, 342 were in patients at increased risk of premalignant lesions, and these were excluded from analysis. Polyps were identified in 172 of the remaining 992 patients (17.3%), whose self-declared ethnicity was: mixed race 76%, white 12%, black African 11%, and Asian 1%. The quality of the bowel preparation and caecal intubation rate was similar between patients with polyps and those without. Individuals with polyps were older than those without polyps (mean age 61. 5 ±12,9 versus 56.3 ±17,4 years, p< 0.002). On histology of these polyps, 119 were adenomas, 26 hyperplastic and 27 normal. The majority of the adenomas were tubular (80%), and only 6% had high grade dysplasia. Half (51%) of the adenomas were in the proximal colon, and the overall adenoma detection rate was 12%. The adenoma detection rate (prevalence) was highest in white, and Asian South Africans (18% each), followed by mixed race (13%), and much lower in black South Africans (5%). Conclusions This study provides a benchmark adenoma detection rate for our catchment population and potentially across Africa. There is evidence of a continuing differential colorectal neoplasia risk according to ethnicity, with fewer adenomas being detected in black South Africans.